Prosedur Penatalaksanaan Computed Tomography (CT Scan) Os. Cruris Dengan Klinis Suspect Tumor Di Unit Radiologi - Annisa, Aulia; Syahputra, M. Syawal (Innovative: Journal Of Social Science Research, 2025)
Computed Tomography (CT) Scan is one of the X-ray diagnostic modalities that utilizes X-rays to display cross-sectional slices of the body on a computer screen. One of the CT Scan examinations is a lower extremity CT Scan. One of the parameters in a CT Scan is Slice Thickness. The slice thickness value will affect the quality of the CT scan image. In general, thick images will have less detail than thin images. In previous journals, slice thicknesses of 1-2 mm were used, while the results of observations in this study used 3 mm. The purpose of this study was to determine the CT Scan Procedure for Cruris with Clinical Tumor Suspects.The type of research used in this study is descriptive qualitative research with a case study approach. Data collection was carried out through observation, interviews, and documentation. The research time started from October 21 to November 30, 2024. The results of the study of the CT Os Cruris examination procedure for parameters using the selected axial slice thickness were 3 mm and 1 mm for sagittal and coronal sections.